The SPIRIT AND LAMENT - Minggus Minarto Pranoto (Jurnal Amanat Agung, 2021)
Abstract: This article aims to explain about lament from the perspective of psychology and pneumatology. Psychology helps to explain psychic state of one who laments because of experiencing grief and bereavement; and pneumatology understands lament theologically by seeing and knowing God, self, and the world through the experience with the Holy Spirit in the believers. The two perspectives above are synthesized to understand the lament in the context of the life of believer. The method used is an interdisciplinary study between psychology and pneumatology by looking for connecting points that might fill and complement each other, especially in explaining the lament of believer. The thesis of this article is that the act of lament is a self-actualization of believer which can be explained from a psychology-pneumatology perspective and in lament the Holy Spirit transforms the life of believer. Lamentation can lead to an attitude of trust in God and the courage to continue with life again or, in psychologically term, a "restoration-oriented” life. Keywords: Spirit/Holy Spirit, lament, psychology, pneumatology, transformation. Abstrak: Artikel ini bertujuan untuk menjelaskan perihal ratapan dari perspektif psikologi dan pneumatologi. Psikologi membantu untuk menjelaskan keadaan psikis orang yang meratap karena sedang mengalami kedukaan (grief) dan kehilangan (bereavement); dan pneumatologi memahami ratapan secara teologis dengan cara melihat dan mengenal Allah, diri, dan dunia melalui pengalaman dengan Roh Kudus. Kedua perspektif di atas disintesiskan untuk memahami ratapan dalam konteks kehidupan orang beriman. Metode yang dipakai adalah studi interdisipliner antara psikologi dan pneumatologi melalui mencari poin-poin penghubung yang mungkin saling mengisi dan melengkapi terutama dalam menjelaskan ratapan orang-orang beriman. Pernyataan tesis tulisan ini adalah tindakan ratapan merupakan sikap mengaktualkan diri dari orang beriman yang dapat dijelaskan dari perspektif psikologi-pneumatologi dan di dalam ratapan Roh Kudus mentransformasi hidup orang beriman. Ratapan dapat membawa kepada sikap percaya kepada Allah yang semakin mendalam dan berani melanjutkan kehidupan kembali atau istilahnya secara psikologi memiliki “restoration-oriented.” Kata-kata kunci: Roh/Roh Kudus, ratapan, psikologi, pneumatologi, transformasi.